2020
DOI: 10.1016/j.psj.2020.06.073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different rearing systems on intramuscular fat content, fatty acid composition, and lipid metabolism–related genes expression in breast and thigh muscles of Nonghua ducks

Abstract: Rearing system is a critical nongenetic factor influencing meat quality of ducks. In this study, a total of 360 birds were randomly allocated into floor rearing system ( FRS ) and net rearing system ( NRS ) to compare their effects on intramuscular fat ( IMF ) deposition, fatty acid composition, and related gene expression in muscles of Nonghua ducks. Sawdust bedding and stainless mesh bed were equipped in FRS and NRS, respectively. At the ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Sex differences are associated with growth performance in chickens [ 9 ], and genetic studies have reported that muscle characteristics, such as fiber CSA, have high heritability (>0.40) and exhibit significant positive genetic correlations with body and muscle weights in broilers between 4 and 6 weeks [ 13 ]. Moreover, muscle morphology is affected by many factors, such as breed [ 14 ], muscle type [ 10 ], age [ 11 , 13 , 15 ], and gene polymorphism [ 11 ]. In the present study, the muscle morphological characteristics of the breast and thigh muscles were assessed at different developmental stages, and the CSA of the breast and thigh muscles increased with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex differences are associated with growth performance in chickens [ 9 ], and genetic studies have reported that muscle characteristics, such as fiber CSA, have high heritability (>0.40) and exhibit significant positive genetic correlations with body and muscle weights in broilers between 4 and 6 weeks [ 13 ]. Moreover, muscle morphology is affected by many factors, such as breed [ 14 ], muscle type [ 10 ], age [ 11 , 13 , 15 ], and gene polymorphism [ 11 ]. In the present study, the muscle morphological characteristics of the breast and thigh muscles were assessed at different developmental stages, and the CSA of the breast and thigh muscles increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal is to provide high levels of growth performance and quality of their meat. The development and composition of breast and thigh muscles, as the main meat-producing parts of chickens, are affected by breed [ 6 ], sex [ 7 ], nutrition [ 8 ], intestinal microbial species [ 9 ], and rearing systems [ 10 ]. Chicken is a favorite food product for healthy eating because it contains higher levels of protein as well as lower fat content than other meats.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase of pigeon age, the moisture content gradually decreased, while the fat content showed a bell‐shaped curve, and reached the maximum value at 28 days. The edible and nutritional value of animal meat was related to protein, fat, and water content, which were closely related to tenderness and juiciness of meat (Guo et al, 2020). Thus, 28‐day‐old pigeons were richer in fat and water content.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, muscle ber types are de ned by the isoforms of myosin heavy chain (MHC) as MyHC I, IIa, IIb, and IIx, based on their different ATPase types [10]. The gene expression related to the intramuscular fat metabolism, such as PPARγ, CPT1,SREBP1, etc., was affected by rearing systems [11]. Different rearing environments may also impact the lipid, protein, and energy metabolism in skeletal muscle by modulating the mechanistic target of the rapamycin (mTOR) signaling pathway [12].…”
Section: Introductionmentioning
confidence: 99%